Assessing the level of risk among hikers at Gunung Baling, Kedah - Ramli, Mohamad Redzuan (2018)
Gunung Baling was rarely known to hikers or even locals. It began to be a popular mountain after it became viral on social media in 2015 because of its beautiful scenery. Since then, many hikers have visited Gunung Baling and the number of accidents reported has also increased. This is because, hikers hike Gunung Baling without notifying the Baling District Council at Gunung Baling. Thus, this study was conducted to assess the level of risk among hikers. A total of 160 questionnaires were distributed to hikers during the data collection period. The data collected includes: (1) respondents socio-demographic factors, (2) hikers visit information and (3) the perception of hikers toward risk at Gunung Baling. The results of this study showed that hikers feel safe hiking Gunung Baling (M = 3.91), but hikers also feel that the peak of Gunung Baling is unsafe (M = 2.94), this is because the surface of the area is rocky and slippery. Hikers agree that to reduce risk when hiking at Gunung Baling, it is important to inform Baling District Council and to place relevant offices at starting point of the mountain. This is because the signage is not effective in reducing risk as signages are unclear, damage and insufficient.